Integrated Health Care Systems and Indigenous Medicine: Reflections from the Sub-Sahara African Region - Ahlberg, Beth Maina (Frontiers in Sociology, 2017)
Indigenous or traditional medicine has, since the 1970s, been widely regarded as a resource likely to contribute to strengthening the health care systems in low income countries. This paper examines the state of traditional medicine using evidence from three case studies in Central Kenya. While the cases are too few to represent the broad diversity of cultures and related healing systems in the Sub-Sahara African Region, the way they seem to refute the main assumptions in the integration discourse is important, also because studies from other countries in the region report perspectives, similar to the case studies in Kenya. It is often argued that people continue to use traditional medicine because it is affordable, available and culturally familiar. Its integration into the health care system would therefore promote cultural familiarity. The case studies however point to the loss of essential cultural elements central to traditional medicine in this particular area while users travel long distances to reach the healers. In addition, there are significant paradigm differences that may present obstacles to integration of the two systems. More problematic however is that integration is, as in many development interventions, a top-down policy which is rarely based on contextual realities and conditions. Instead, integration is often defined and dominated by biomedical professionals and health planners who may be unfamiliar or even hostile to some aspects of traditional medicine. Furthermore, integration efforts have tended to embrace selected components mostly herbal medicine. This has led to isolating herbal medicine from spiritualism, which may in turn affect the holistic perspective of traditional medicine. While familiarity and relevance may explain the continued use of traditional medicine, its services may not be as readily available, accessible or even affordable as is often asserted. Globalisation set in motion through colonization and ensuing modernization processes, including urbanization, education, religion and a neo-liberal economic system, have introduced a social order creating physical as well as social distances between users of traditional medicine and the healers.